1998
DOI: 10.1080/00365529850166194
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Gastric Ulcer Recurrence with Tetraprenylacetone

Abstract: Treatment with TAP plus omeprazole significantly decreases ulcer recurrence through TAP's improved mucosal restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…One pharmacological inducer of Hsps is geranylgeranylacetone (GGA). GGA has been safely used in Japan in the clinical treatment of gastric ulcers (Shirakabe et al 1995;Nagasawa et al 1998;Miyake et al 2004;Qian et al 2007). GGA has been shown to induce Hsp70 in variety of tissues, including the gastric mucosa, heart, liver, brain, and cochlea (Hirakawa et al 1996;Ooie et al 2001;Oda et al 2002;Mikuriya et al 2005;Sone et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One pharmacological inducer of Hsps is geranylgeranylacetone (GGA). GGA has been safely used in Japan in the clinical treatment of gastric ulcers (Shirakabe et al 1995;Nagasawa et al 1998;Miyake et al 2004;Qian et al 2007). GGA has been shown to induce Hsp70 in variety of tissues, including the gastric mucosa, heart, liver, brain, and cochlea (Hirakawa et al 1996;Ooie et al 2001;Oda et al 2002;Mikuriya et al 2005;Sone et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…GGA was originally developed as a mucosal protecting agent 20 years ago [24], and several mechanisms of its protection against noxious agents have been proposed. Earlier, it was reported [25] that GGA stimulates the mucus production by gastric mucosal cells, other studies [16, 17], however, have shown that the protective effect of GGA on the gastric mucosa is not abolished by NSAIDs which are known to inhibit the mucus production.…”
Section: Discussionmentioning
confidence: 99%
“…Dental plaque has been implicated as a source of H. pylori by studies that used culture [1, 2, 26], biochemical tests [2, 26], nucleic acid analysis [20, 23, 27, 28, 29], and immunological assays [30, 31]. Several studies revealed a high prevalence of H. pylori in the oral cavity of people in developing countries, whereas in industrialized countries neither dental plaque nor dentures seemed to be an important reservoir for H. pylori .…”
Section: Discussionmentioning
confidence: 99%